Targeting Epigenetics and Non-coding RNAs in Myocardial Infarction: From Mechanisms to Therapeutics - Chen, Jinhong; Liu, Zhichao; Ma, Li; Gao, Shengwei; Fu, Huanjie; Wang, Can; Lu, Anmin; Wang, Baohe; Gu, Xufang (Frontiers in Genetics, 2021)
Myocardial infarction (MI) is a complex trait to which multiple environmental and genetic factors contribute. Understanding the role of epigenetic regulation mechanisms in cardiovascular disease, would advance the field and promote disease prevention approaches that are aimed to target epigenetic mechanisms. Genetic screening could be an approach for guiding individualized therapies and surveillance for MI. In this review, we summarize recent advances in the understanding of the epigenetic regulation of MI in terms of DNA methylation, histone modifications, and microRNA-dependent mechanisms in MI and the novel epigenetics-based therapeutic approaches.